Jamaicans’ National Identity - Phillips, Rupert (The international journal of religion and spirituality in society, 2014)
This paper will discuss the relationship between religion and national identity in Jamaica. Pan-Africanists argue that slavery created a feeling of racial identity among Negroes in Jamaica. Though, the feeling of religious identity that Christianity created among West Africans in Jamaica has been missed, negated, or put on the periphery by this model. This paper discusses two main points: (a) structural Christianizing of Negroes in Jamaica; and (b) how did Negroes actively incorporate European Christianity in their lives? To answer these questions, I reviewed the works of three well-recognized black Jamaican scholars: Horace Campbell, Pan-Africanist; Aggrey Brown, black power advocate; and Don Robotham, a Marxist and black working-class advocate. I argue that, through education and practice, Christianity provided the unifying concept of a Creator who designed and upheld the universe; subsequently, a national community among polytheist West Africans and/or Negroes in Jamaica was created. This paper also posit: (a) a counter-discourse to conventional black Anglophone Caribbean and Jamaican scholarship that suggests that race is the source of black Jamaicans’ national identity; (b) an essay on ideas and interpretations of European Christianity in Jamaica covering the period 1754-1854; (c) that Nonconformist European Christianity deserves a primary place in the larger project of discovering the national identity in Jamaica; and (d) that this collective birthright of black Jamaicans and deserves to be broadly known. The paper is significant because it adds to the black slave literature about the emergence of primarily tribal West Africans into a cohesive, collective identity as Jamaicans under European slavery in the New World. Implications of this paper include the following discussion: current black, English-speaking Caribbean/Jamaican views and scholarly works are monolithic or one-sided on the subject of the Caribbean/Jamaican identity. What is specifically ignored or negated in the literature is the civilizing influence that European Christianity provided in Jamaica.